PENGORGANISASIAN GUGUS DEPAN PRAMUKA UNIVERSITAS RIAU - Rahmadani Harahap; Daeng Ayub Natuna; Desti Irja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: This research is backgrounded by the scout organization under the University environment, due to unnecessary and irregular student schedule which where the student yag has become a member rarely participate in the activity. The formulation of this research problem is how the process of organizing the Riau University scout front group? Know how the process of organizing Scout University of Riau in the world of Organizations that take refuge under Higher Education. This organizing indicator is a function of organizing, organizing process, organizing principles, and organizing principles. This data collection uses documentation, observation, and interview techniques. The results will be presented and described in the form of sentences, explanations, or statements meaningful to organize the front group of Scouts of Riau University.Keyword: Organization, Scout